Use of Botanical Extracts against Pulse Beetle (Callosobruchus chinensis l.) in Stored Chickpea in Laboratory Condition - Bhattarai, Roshani; Gurung, Nischal; Singh, Narendra Bahadur; Dawadi, Bishnu (Journal of the Institute of Agriculture and Animal Science, 2024)
Pulse beetle (Callosobruchus chinensis L.) is an economic pest of stored pulses. The chemicals used for seed protection create human health and environmental risks. Thus, an experiment was conducted to test the efficacy of locally available botanicals as an alternative against pulse beetle in chickpeas at the entomology laboratory of Lamjung Campus from April to June 2023. Eight treatments comprising untreated control and powdered botanicals like leaves of Azadirachta indica A. Juss., Ocimum sanctum L., and Cinnamomum tamala Buch.-Ham., the rhizome of Acorus calamus L. and Curcuma longa L., seed of Zanthoxylum armatum DC. and fruit of Capsicum annum L. were replicated three times in completely randomized design. Treatments were prepared by mixing botanicals at a rate of 0.5 grams per 50 grams of chickpea. newly emerged pulse beetle adults were used in each treatment. Weevil mortality was observed every two days. Progeny emergence was recorded from the 25th to 42 days. Weight loss and percentage of damaged seeds were recorded at the end of the experiment. All the botanicals differed significantly from the control in weevil mortality starting at 6 days of treatment application along with weight loss, seed damage and progeny deterrence which were assessed at the end of experiment. Among the botanicals, A. calamus and Z. armatum showed superior performance achieving 100% weevil mortality by the sixth day of treatment, while completely preventing seed damage and exhibiting 100% progeny deterrence and lowest weight loss. Hence, botanicals can manage beetles during pulse storage.